An eye emergency at high altitude on the climber: things not to miss (Bangladesh Journal of Medical Science, 2014)
Risk of eye emergencies at high altitude should be noted by Emergency Physicians or expedition doctors for high altitude missions. Early management and understanding the sequelae of the conditions will make a difference in management and decisions at high altitude. DOI: http://dx.doi.org/10.3329/bjms.v13i3.16099 Bangladesh Journal of Medical Science Vol.13(3) 2014 p.353-355